2015
DOI: 10.1093/chemse/bjv007
|View full text |Cite
|
Sign up to set email alerts
|

Obese Individuals Have Higher Preference and Sensitivity to Odor of Chocolate

Abstract: The worldwide epidemic of obesity has inspired a great deal of research into its causes and consequences. It is therefore surprising that so few studies have examined such a fundamental part of eating behavior: our sense of smell. The aim of the present study was to examine the differences in olfaction in obese and nonobese individuals. Participants (n = 40) categorized as obese (body mass index ≥ 30) or nonobese (body mass index < 30) completed a standardized olfactory threshold test to an ecologically valid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 35 publications
2
61
1
3
Order By: Relevance
“…Some studies reported a decrease in olfactory sensitivity with increasing BMI in adults (2830), whereas another study in children reported an increase in olfactory sensitivity with increasing BMI (31). Moreover, recent studies have shown that adults with obesity were better at detecting food odors than adults without obesity (32, 33). In summary, there is no strong evidence of a difference in the ability to properly identify food odors according to a subject’s weight status, whether the subjects are adults or children.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a decrease in olfactory sensitivity with increasing BMI in adults (2830), whereas another study in children reported an increase in olfactory sensitivity with increasing BMI (31). Moreover, recent studies have shown that adults with obesity were better at detecting food odors than adults without obesity (32, 33). In summary, there is no strong evidence of a difference in the ability to properly identify food odors according to a subject’s weight status, whether the subjects are adults or children.…”
Section: Discussionmentioning
confidence: 99%
“…The odour used for the threshold test was a sweet smelling chocolate odourant (Code 0679, Anglo brands, UK) used in previous work (Stafford and Whittle, 2015) which was diluted in propylene glycol (Fisher Scientific, UK). The odourant was prepared using sixteen 250ml squeeze bottles, in 16 dilution steps, starting at 0.125% (Step 1) with each successive step diluted by a factor of two using serial dilution to the lowest (Step 16) dilution.…”
Section: Olfactory Threshold Testmentioning
confidence: 99%
“…This may be due to changes in olfactory sensory neurons (OSNs), with a decline of OSNs shown to occur over time during high-fat intake in animal studies [ 25 ]. In contrast, another study found participants with obesity had a stronger hedonic response towards the smell of dark chocolate than non-obese participants, rating the odour as significantly more pleasant [ 26 ]. Furthermore, there is emerging evidence that variations in human olfactory receptor gene expression can influence eating behaviour, resulting in increased adiposity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%